Metabolic status is associated with the recovery of milk somatic cell count and milk secretion after lipopolysaccharide-induced mastitis in dairy cows - Gross, J.J.; Grossen-Rösti, L.; Wall, S.K.; Wellnitz, O.; Bruckmaier, R.M. (Journal of dairy science, 2020)
Infections of the mammary gland in dairy cows are commonly accompanied by reduced milk production and feed intake and poor milk quality. The metabolic status of early-lactating cows is known to affect immune response to pathogens and imposed immune challenges. We investigated the extent to which metabolic status before an intramammary lipopolysaccharide (LPS) challenge (LPS-CH) is associated with immune response, milk production, and feed intake and the recovery thereof. In 15 Holstein cows, weekly blood sampling and daily recording of dry matter intake, milk yield, milk composition, and body weight (to calculate energy balance) was started immediately after parturition. In wk 4 after parturition, cows underwent an intramammary LPS-CH (50 μg of LPS into 1 quarter). Blood and milk samples were taken in parallel at 30- and 60-min intervals, respectively, until 10 h after the LPS application. Plasma concentrations of glucose, nonesterified fatty acids, β-hydroxybutyrate (BHB), cortisol, and insulin were analyzed. In milk, serum albumin, IgG concentration, somatic cell count (SCC), and lactate dehydrogenase (LDH) activity were determined. Dry matter intake and milk yield were recorded for an additional 6 d. Milk of the LPS-treated quarter was sampled at every milking for 8 d after the challenge. Based on plasma glucose concentrations in wk 1 to 4 after parturition before the LPS-CH, cows were retrospectively grouped into a high-glucose group (HG; 3.34–3.93 mmol/L, n = 7) and a low-glucose group (LG; 2.87–3.31 mmol/L, n = 8). Data were evaluated using mixed models with time, group, and time × group interaction as fixed effects and cow as repeated subject. Glucose was lower and BHB was higher in LG compared with HG before LPS-CH, whereas dry matter intake, energy balance, and SCC did not differ. During LPS-CH, SCC and LDH increased similarly in HG and LG, body temperature increased less in HG, and BHB and nonesterified fatty acids were higher in LG compared with HG. Dry matter intake declined in both groups during the day of the LPS-CH but recovered to prechallenge values faster in HG. Milk yield recovered within 2 d after the LPS-CH with no differences in morning milkings, whereas evening milk yield increased faster in HG. During 8 d after LPS-CH, SCC, LDH, IgG, and serum albumin in milk were lower in HG compared with LG. In conclusion, the level of circulating glucose and BHB concentrations in cows was associated with metabolic responses during an LPS-CH as well as the recovery of udder health and performance thereafter.